Peran Surat Berharga Sebagai Instrumen Penggajian Terhadap Komponen Hukum Ketenagakerjaan - Nikmah Dalimunthe; Tazkia Ayu Alharani.YS; Putri Amanda; Putri Indriyanti; Sri Nurul Hasanah; Muhammad Sholeh Khan; Muhammad Akbar Al-Ghifari Barus; Anhar Nurdiansyah Harahap (Jurnal Manajemen Riset Inovasi, 2023)
This study aims to analyze the role of securities as payroll instruments and legal components in the context of employment. This research uses qualitative methods while the type of research is descriptive. The results of this study indicate that securities as a payroll instrument are used as an effective payroll tool in the context of employment. Companies can issue securities in the form of investments to employees as a form of additional remuneration or incentives, such as company stock, bonds, or stock shares. While securities in the context of labor law that the use of securities as a remuneration instrument also has legal implications in the context of employment